Study of Er3+ fluorescence on tellurite glasses containing Ag nanoparticles - Rivera, V. A G; Manzani, D. [UNESP]; Messaddeq, Younes [UNESP]; Nunes, L. A O; Marega, E. (IOP Publishing, 2011)
Optical characteristics of tellurite glasses containing silver nanoparticles (NPs) and the influence on the emission spectrum of Er 3+ ions were studied. The transitions 4f ↔ 4f from erbium ions, mainly the 4I13/2 → 4I15/2 transition that involve upconversion energy process, have a strongly dependence with the chemical structure of the rare earth ion. In the present work, silver nanparticles (NPs) embedded in the host vitreous material, show a significant enhance (or quenching) on the erbium fluorescence due the long-range electromagnetic interaction between the plasmon surface energy of the Ag NPs (Localized Surface Plasmon Resonance -LSPR) and the Er3+ ions.
Keywords: Ag nanoparticle; Chemical structure; Electromagnetic interactions; Emission spectrums; Energy process; Erbium ion; Localized surface plasmon resonance; Optical characteristics; Rare earth ions; Silver nanoparticles; Surface energies; Tellurite glass; Up-conversion; Vitreous materials; Emission spectroscopy; Erbium; Fluorescence; Glass; Metal ions; Nanoparticles; Plasmons; Surface chemistry; Surface plasmon resonance; Silver